Uppermost mantle and crustal structure at Tristan da Cunha derived from ambient seismic noise - Ryberg, T.; Geissler, W.H.; Jokat, W.; Pandey, S. (My University, 2017)
According to classical plume theory, the Tristan da Cunha hotspot, located ∼400 km east off the MidAtlantic Ridge, is thought to have played a major role in the rifting while creating an aseismic Walvis Ridge during and after the breakup of the South Atlantic margins. Volcanic activity on the Tristan da Cunha Island shows that the hotspot might still be there influencing the upper mantle and crustal structure. In this study we present ambient noise data from 24 broadband OBS around Tristan da Cunha and a seismic station on Nightingale Island, which provide first constraints on the crustal and uppermost mantle structure around the island. By combining ambient noise techniques, dispersion curve analysis of Rayleigh waves, 2D tomographic inversion of travel times and 3D depth inversion of dispersion data we derived a 3D VS velocity model around the archipelago of Tristan da Cunha. The model shows an isolated, vertically sharp bounded thickened and modified crust beneath the islands surrounded by thin oceanic crust (<5 km). The velocity anomaly shows a typical volcanic structure with a shallow high velocity body and a low velocity root reaching into the upper mantle, which we interpret as shallow solidified magmatic material and volcanic feeding system/magmatic underplating, respectively. The observed simple and localized volcanic structure, embedded in a rather homogeneous crust and upper mantle indicates only minor and very localized magmatic overprinting of the existing lithosphere by the Tristan da Cunha hotspot. The uppermost mantle S wave velocity beneath nearby seamounts and to the SW of the islands is also slow and could indicate a thermal influence from a deeper source, whereas the Tristan da Cunha Fracture Zone shows no signs of modification.
Keywords: Hotspot volcanism; Ambient seismic noise; Surface wave tomography; South Atlantic opening; Tristan da Cunha